Resisting Patriarchy through Language: A Faircloughian Critical Discourse Analysis of Melawan Bahasa Patriarki - Ida Ayu Trisna Adiwulandari Ida Ayu Trisna; I Nyoman Darma Putra; Ade Prameswari Angelita (Soshum: Jurnal Sosial dan Humaniora, 2026)
Language functions not only as a medium of communication but also as a site where ideology and power relations are produced and contested. This study examines how patriarchal ideology is both constructed and resisted in Chapter V of Putu Pratiwi’s Melawan Bahasa Patriarki, entitled “Liberation of Women from Patriarchal Language Today.” Drawing on Norman Fairclough’s three-dimensional model of Critical Discourse Analysis, the research analyses the text at the levels of textual features, discursive practice, and socio-cultural practice. Using a qualitative approach, selected excerpts are examined with attention to lexical choices, transitivity, sentence mood (affirmative and imperative constructions), modality, and intertextuality. The findings indicate that patriarchal ideology is embedded in gender-marked vocabulary and epistemic modalities that normalise male-centred perspectives. At the same time, the text constructs resistance through imperative appeals, the redefinition of feminine identity, and the introduction of alternative terminology. Discursively, readers—particularly women—are positioned as active agents of resistance. Socio-culturally, the analysis shows how linguistic practices both reflect and challenge broader patriarchal structures. This study contributes to Critical Discourse Analysis and feminist linguistics by demonstrating how linguistic microstructures interact with social contexts to sustain and resist patriarchal power in contemporary Indonesian discourse.